Fire regimes approaching historic norms reduce wildfire‐facilitated conversion from forest to non‐forest - Walker, Ryan B.; Coop, Jonathan D.; Parks, Sean A.; Trader, Laura (Ecosphere (Washington, D.C), 2018)
Extensive high‐severity wildfires have driven major losses of ponderosa pine and mixed‐conifer forests in the southwestern United States, in some settings catalyzing enduring conversions to non‐forested vegetation types. Management interventions to reduce the probability of stand‐replacing wildfire have included mechanical fuel treatments, prescribed fire, and wildfire managed for resource benefit. In 2011, the Las Conchas fire in northern New Mexico burned forested areas not exposed to fire for >100 yr, but also reburned numerous prescribed fire units and/or areas previously burned by wildfire. At some sites, the combination of recent prescribed fire and wildfire approximated known pre‐settlement fire frequency, with two or three exposures to fire between 1977 and 2007. We analyzed gridded remotely sensed burn severity data (differenced normalized burn ratio), pre‐ and post‐fire field vegetation samples, and pre‐ and post‐fire measures of surface fuels to assess relationships and interactions between prescribed fire, prior wildfire, fuels, subsequent burn severity, and patterns of post‐fire forest retention vs. conversion to non‐forest. We found that Las Conchas burn severity was lowest, and tree survival was highest, in sites that had experienced both prescribed fire and prior wildfire. Sites that had experienced only prescribed or prior wildfire exhibited moderate burn severity and intermediate levels of forest retention. Sites lacking any recent prior fire burned at the highest severity and were overwhelmingly converted to non‐forested vegetation including grassland, oak scrub, and weedy, herbaceous‐dominated types. Burn severity in the Las Conchas fire was closely linked to surface woody fuel loads, which were reduced by prior wildfire and prescribed fire. Our results support the restoration of fire regimes via prescribed fire and resource benefit wildfire to promote the resiliency of forest types vulnerable to fire‐mediated type conversion. The application of prescribed fire to reduce surface fuels following wildfire may reduce forest loss during subsequent fire under more extreme conditions. These findings are especially relevant given likely increases in vulnerability associated with climate change impacts to wildfire and forest dynamics.